High‐gain tapered slot antenna with spoof surface plasmon polaritons director. Issue 19 (27th July 2022) - Zheng, Zichao; Chen, Fangjun; Pan, Ziyu; Xu, Feng
Abstract: In this letter, the authors propose a high‐gain and low‐profile tapered slot antenna (TSA) with a composite patch made of ellipse and spoof surface plasmon polaritons (sSPPs) structures. The authors first demonstrate the construction details and associated dimensions of the antenna fabrication. Then the authors discuss the role of the patch, which is placed at the antenna's radiating opening to improve the directivity of the antenna. Measurements of the fabricated antenna show a wide operating bandwidth of 82.3% (5–12 GHz) is achieved. The gain of the antenna varies from 5.2 to 13.4 dBi, in which radiation patterns show good directivity and end‐fire radiation performance. The measured results are in good agreement with the simulation results, indicating that the antenna performance has been improved as expected by adopting this design.